2004
DOI: 10.4081/ijas.2004.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the proportion of Duroc genes in crosses with Large White and Landrace pigs on the characteristics of seasoned Parma ham

Abstract: The aim of this study was to estimate the linear and quadratic effects of the proportion of Duroc genes on the characteristics of seasoned Parma hams by means of a covariance model. The study was carried out on 167 pigs (87 castrated males, 80 females) from different crosses among Duroc (D), Large White (LW) and Landrace (L) breeds, slaughtered at 300 d of age (live weight 170 kg). All pigs were raised under similar conditions. The curing period was 380 days. The proportion of Duroc genes was 0% (LWxL; n. 33),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The differences in the ham traits of the Duroc and Large White breeds observed in this study are in agreement with the results obtained by Schivazappa et al (2002), Bosi and Russo (2004) and Sabbioni et al (2004). Furthermore, some studies have reported significant differences among the ham of animals of the Duroc and Large White breeds in the quantity of ham after deboning, such that Duroc breed animals gave the highest yields (Franci et al, 1997;Sabbioni et al, 2004).…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…The differences in the ham traits of the Duroc and Large White breeds observed in this study are in agreement with the results obtained by Schivazappa et al (2002), Bosi and Russo (2004) and Sabbioni et al (2004). Furthermore, some studies have reported significant differences among the ham of animals of the Duroc and Large White breeds in the quantity of ham after deboning, such that Duroc breed animals gave the highest yields (Franci et al, 1997;Sabbioni et al, 2004).…”
Section: Discussionsupporting
confidence: 95%
“…Sabbioni et al (2004) observed differences in ham weight between 50% Duroc and Large White  Landrace animals in the 160-170 kg harvest weight range. Thus, the hypothesis may be considered that the data structure, specifically in the set of ham measurements harvested at 160 kg (limited number of WIWI and no DUDU genetic group), influenced the results obtained.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations